HUBUNGAN MANIFESTASI KLINIS ASMA DENGAN KUALITAS HIDUP ANAK - , SRI PURWATI, Dr.Dra.I.L. Gamayanti, Msi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bronchial asthma is the most common chronic disease in children. Asthma affects the quality of life of children. This study aims to determine the difference in quality of life of children with asthma based on the degree and the degree of asthma attacks. This study with a design divided conducted in the department of Child Health Dr. Sardjito General Hospital from January to October 2011. Fifty-one children with asthma consisted of 32 males and 19 females, aged 7-17 years were consecutively involved . Assessment of quality of life used the Pediatric Asthma Quality of Life Questionnare (PAQLQ). The average score of quality of life of asthma children with mild attack was 4.43 (SD 0.44), whereas for severe was 4.42 (SD 0.38). Based on degree of illness the average score of quality of life with frequent episodic attacks was 4.36 (SD 0.38), while the rare episodic attacks was 4.47 (SD 0.43). There was no difference quality of life in children with asthma based on the degree of asthma attacks There was no difference in total score of quality of life in children with asthma based on the degree of illness, but there are differences in the domains of symptoms of asthma quality of life in children with frequent and rare attacks (mean difference - 0.28